CORRELATION BETWEEN LEARNING MOTIVATION AND STUDENT’S LEARNING ACHIEVEMENT IN HISTORY SUBJECTS AT SMA NEGERI 1 PALELEH BARAT - Risnawati S. Dalingo; Resmiyati Yunus; Iis Husnul Hotimah (CV. Fahr Publishing, 2026)
This research endeavor seeks to elucidate the degree of correlation between the motivational factors influencing students' learning and their corresponding academic performance in history courses at SMA Negeri 1 Paleleh Barat. The methodological framework employed in this investigation is grounded in a quantitative paradigm, utilizing correlational analytical techniques. Primary data were systematically gathered through the administration of structured questionnaires and interviews conducted with history educators and students, while secondary data were derived from a diverse array of scholarly literature and pertinent informational resources. The methodologies employed for the purpose of data acquisition comprised observational studies, qualitative interviews, structured questionnaires, and the analysis of relevant documentary sources. The results of this investigation revealed a statistically significant relationship between the learning motivation of students and their academic performance. This is substantiated by a correlation coefficient of 0.620, signifying 62%. Furthermore, the coefficient of determination was computed to be 38.5%, which suggests that learning motivation is responsible for 38.5% of the variability observed in student academic achievement, while the remaining 61.5% is attributable to external variables not examined within the scope of this research. Consequently, it can be deduced that learning motivation is a crucial determinant in the improvement of student performance in history courses at SMA Negeri 1 Paleleh Barat.